KONVERSI INSTITUSIONAL IAIN MENUJU UIN ALAUDDIN MAKASSAR MENURUT PERSPEKTIF AZHAR ARSYAD - Muhammad Rais (EDUCANDUM, 2017)
This article is projected to describe the process of institutional status transfer of IAINto UIN Alauddin Makassar according to Azhar Arsyad's perspective, which is one ofthe initiators of the transformation process of the State Islamic University. By utilizingthe social history approach, specifically the intellectual / historical history, this studyexamines the main points of thought Azhar with regard to the siginifikansi discoursewith respect to the importance of wider mandate of State Islamic University. which hasbeen using institutional nomenclature with all the limitations that are concentrated onthe discourse of the scientific paradigm which tends to be monolithic and atomistic,which is only concerned with Islamic discourse an sich, whose estuaries oftenculminate in the growing dichotomy between science and Islam, which is essentiallylike two inseparable sides of the coin. Taken for granted, Azhar also constructs ascientific integration paradigm, which is actually applied in UIN in the framework ofbreaking the chain which, during the two entities, a dichotomy between science andreligion that is originally like two inseparable coins, if it refers to the scientificparadigm of Islam. Concretely, Azhar is more holistic about the classification ofscience, and which is not spared by Azhar is improving the process of education andlearning in UIN post-institutional transformation